PERUMUSAN STRATEGI UNTUK PENGUKURAN KINERJA BERBASIS BALANCED SCORECARD DI BADAN PENGAWAS TENAGA NUKLIR (BAPETEN) - , Harry Sumitro ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to offer a performance measurement method based on the Balanced Scorecard (BSC) for the Nuclear Energy Regulatory Agency (BAPETEN), in wide organizational level. BAPETEN as government agencies that are not oriented to profit as may be necessary to formulate an appropriate performance measurement in order to realize the mandatory for the bureaucracy reform from the government, with a good goovernance organizational system. The step in the preparation of performance measurement using the BSC method begins by formulating a medium-term and long term alternative strategy, that can be applied based on the results of external and internal analysis organization. Alternative strategies are selected and formulated into a strategy map by dividing the strategic objectives into four perspectives of BSC, consists of learning and growth, internal processes, customers and stakeholders. Targets are defined by strategy must be measurable and easy to communicated in accordance with the targets to be achieved by the organization. After getting the selective measurements, the next step is to determine the initiative strategy to implement the strategy objectives. The result of this research was obtained